+0  
 
0
191
1
avatar
sqrt(y+1) + sqrt(y-3) = 5

i cant solve this confounded problem i need it an example
Guest Feb 28, 2012
Sort: 

1+0 Answers

 #1
avatar+3071 
0
arkansaw:

sqrt(y+1) + sqrt(y-3) = 5

i cant solve this confounded problem i need it an example



sqrt(y + 1) + sqrt(y - 3) = 5
sqrt(y + 1) + sqrt(y - 3) = 5 | -sqrt(y - 3)
sqrt(y + 1) = 5 - sqrt(y - 3) | ^2
y+1 = (5 - sqrt(y - 3) )^2
y+1 = 5^2- 2*5*sqrt(y - 3) + (y - 3)
y+1 = 25- 10*sqrt(y - 3) + (y - 3)
y+1 = 22- 10*sqrt(y - 3) + y | -y
1 = 22- 10*sqrt(y - 3) | -22
-21 = -10*sqrt(y - 3) | *-1
21 = 10*sqrt(y - 3) | /10
21/10 = sqrt(y - 3) | ^2
(21/10)^2 = y - 3 | +3
(21/10)^2 +3 = y
441/100 + 3 = y
441/100 + 300/100 = y
y = 741/100
y = 7.41
admin  Feb 28, 2012

4 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details